Development of a portable information system: connecting palmtop computers with medical records systems and clinical reference resources. - Ram, R. (American Medical Informatics Association, 1993)
The portability of palmtop computers makes them an ideal platform to maintain communication between busy physicians and medical information systems. In our academic FHC (Family Health Center) we have developed software that runs on a palmtop computer allowing access to information in the HIS (Hospital Information System) and our FHC's AAMRS (Automated Ambulatory Medical Record System). The resident physicians who staff the hospital and the FHC are frequently at home or otherwise off-site where terminal access is not available. Using a Hewlett-Packard 95LX palmtop computer as the base platform, custom software has been developed to access summary data on in-patients and out-patients. Data is downloaded into a database on a palmtop computer memory card. ASCII data from Medical Information Systems (MIS), is transformed into a database format readable on the palmtop. Our hospital MIS department transmits information daily on our in-patient service (20-30 patients). We also download, weekly, a patient summary on all of our active out-patients in our MUMPS-based AAMRS (2500-3000 patients). Each morning the resident in the Family Practice program updates his palmtop memory card at a central workstation. Palmtop computers with downloaded databases, can be valuable in care of patients when the physical or on-line chart is not easily accessible. They are particularly useful in multi-physician groups when the on-call physician provides care for the patients of other physicians. We have made the palmtop computer even more valuable to physicians by providing an integrated software package.(ABSTRACT TRUNCATED AT 250 WORDS)